Flares and Predicting Factors of Flares in Patients with Systemic Lupus Erythematosus Associated with Different Doses and Types of COVID-19 Vaccines - Worawit Louthrenoo; Punsita Tangkum; Nuntana Kasitanon; Wanitcha Gumtorntip; Poramed Winichakoon; Supparat Konsamun; Antika Wongthanee (Vaccines)
Objectives: To compare disease activity and flares among different doses and types of COVID-19 vaccines in systemic lupus erythematosus (SLE) patients. Methods: SLE patients in a lupus cohort, who received at least one dose of a COVID-19 vaccine (inactivated virus, adenovirus-vectored, or mRNA vaccines) between March and October 2022 joined this study. The data regarding disease activity and flares after each dose were reviewed and compared. Results: Two hundred and one SLE patients (524 total doses) were included in this study, with 201, 199, and 124 of them receiving 1, 2, and 3 doses of a vaccine, respectively, which comprised 183, 128, and 213 doses of inactivated virus, adenovirus-vectored, and mRNA vaccines, respectively. Regardless of vaccine dose or type, there were no significant changes in SLE disease activity pre- or post-vaccination. Flares were significantly more common after the 2nd and 3rd doses than after the 1st one (20.10% and 17.74% vs. 8.96%, p = 0.001, and p = 0.010, respectively), and after inactivated virus, adenovirus-vectored and mRNA vaccinations in 11.48%, 14.84%, and 17.84% of the patients (p = ns), respectively. However, the incidence rate of flares/100 patient-months was not different. The majority of flares were severe, with renal flares being the most frequent. Renal and mucocutaneous involvement and high SLE disease activity prior to the 1st vaccine dose were independent factors that predicted flares. Conclusions: Flares after COVID-19 vaccination were not uncommon. Most of the flares were severe, mainly due to renal flares. SLE patients should have stable low disease activity prior to receiving COVID-19 vaccine in order to avoid flares.